Identifying experts in the field of visual arts using oculomotor signals - Marcin Kolodziej; Andrzej Majkowski; Piotr Francuz; Remigiusz J. Rak; Paweł Augustynowicz (Journal of Eye Movement Research)
In this article, we aimed to present a system that enables identifying experts in the field of visual art based on oculographic data. The difference between the two classified groups of tested people concerns formal education. At first, regions of interest (ROI) were determined based on position of fixations on the viewed picture. For each ROI, a set of features (the number of fixations and their durations) was calculated that enabled distinguishing professionals from laymen. The developed system was tested for several dozen of users. We used k-nearest neighbors (k-NN) and support vector machine (SVM) classifiers for classification process. Classification results proved that it is possible to distinguish experts from non-experts.